Demand bias as an explanation for structural change - Erich Gundlach (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
An income elastic demand for services is usually regarded as one of the major explanations for the observed pattern of structural change in the world economy. Recent empirical findings cast some doubt on this demand-bias hypothesis. This paper presents a simple model of structural change that allows an assessment of the implications of alternative demand elasticities. The analysis focusses on restrictions for the set of consistent parameter values derived from demand theory. The results show that lagging productivity growth in the service sector and a homothetic or income inelastic demand for services do not suffice to explain the stylized facts.
Keywords: 330